Umiejętności komunikacyjne dzieci z zespołem Downa - JĘDRZEJOWSKA, AGNIESZKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Agnieszka Jędrzejowska, Umiejętności komunikacyjne dzieci z zespołem Downa [Communication skills of children with Down Syndrome]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 201-218. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.12 The purpose of this article is to present the results of research concern setting of functional cooperation with the interlocutor in children with Down syndrome in a peer group. Analysis of the results indicates the relationship between methods of therapy and development of children with Down syndrome. The methods of Alterantive and Augmentative Communication (AAC) are important in achieving success in building relationships for children with problems with verbal communication. Secondly, peer group is important to increase social skills. This research show that children with Downe syndrome need similar friends. This leads to the coclussion that group with homogeneous disability is area of development.